2013
DOI: 10.1038/mp.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acid supplementation changes intracellular phospholipase A2 activity and membrane fatty acid profiles in individuals at ultra-high risk for psychosis

Abstract: The identification of an ultra-high risk (UHR) profile for psychosis and a greater understanding of its prodrome have led to increasing interest in early intervention to delay or prevent the onset of psychotic illness. In a randomized placebo-controlled trial, we have identified long-chain ω-3 (ω-3) polyunsaturated fatty acid (PUFA) supplementation as potentially useful, as it reduced the rate of transition to psychosis by 22.6% 1 year after baseline in a cohort of 81 young people at UHR of transition to psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 54 publications
3
51
0
2
Order By: Relevance
“…It is relevant to note here that PLA 2 activity in serum and CSF are closely correlated (Smesny et al, 2008; Talib et al, 2013). These curvilinear relationships support the notion that there might be an optimum of physiological in PLA 2 activity and membrane LC-UFA turnover associated with healthy WM myelination (Smesny et al, 2014), while excessive in PLA 2 activity may reduce WM myelination. This is in line with findings of increased in PLA 2 activity being associated with structural brain WM abnormalities in patients with schizophrenia including first-episode patients (Smesny et al, 2010).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It is relevant to note here that PLA 2 activity in serum and CSF are closely correlated (Smesny et al, 2008; Talib et al, 2013). These curvilinear relationships support the notion that there might be an optimum of physiological in PLA 2 activity and membrane LC-UFA turnover associated with healthy WM myelination (Smesny et al, 2014), while excessive in PLA 2 activity may reduce WM myelination. This is in line with findings of increased in PLA 2 activity being associated with structural brain WM abnormalities in patients with schizophrenia including first-episode patients (Smesny et al, 2010).…”
Section: Discussionsupporting
confidence: 75%
“…Polyunsaturated fatty acids (PUFAs) are important components of the phospholipid bilayers of cell membranes including those of oligodendrocytes. There is active turnover of PUFAs in cellular membranes, which is regulated by intracellular phospholipase A 2 ( in PLA 2 ), a group of enzymes catalyzing the cleavage of fatty acids from the sn-2 position of phospholipids (Smesny et al, 2014). Each PLA 2 enzyme specifically catalyzes the hydrolysis of the center (sn-2)- ester bond of substrate phospholipids and supplies PUFAs downstream to cyclooxygenase and lipoxygenase that in turn transform fatty acids into a group of biomediators called eicosanoids (please see appendix A for additional information on in PLA 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our own research on the role of intracellular phospholipase A2 (inPLA2) in ultra‐high risk subjects has shown that levels of membrane omega‐3 and omega‐6 PUFAs and inPLA2 activity were strongly correlated. However, some of the significant associations were in opposite directions in individuals who did (a positive correlation) and who did not (a negative correlation) transition to psychosis . These findings are suggestive of ongoing changes in the interactions of membrane metabolic markers during the course of the ultra‐high risk phase of illness (stage 1b).…”
Section: Fatty Acid Markersmentioning
confidence: 89%
“…The effectiveness of ω3 fatty acids has also been evaluated in the treatment of bipolar depression, where two of three placebo-controlled, double-blind trials found a beneficial effect over placebo (Clayton et al , 2009, Stoll et al , 1999). This effect may be related to the regulation of intracellular phospholipase A2 activity (Smesny et al, 2013). In addition, ω3 fatty acid treatment was also beneficial in the treatment of schizophrenia (Nakagome et al , 2009, Peet, 2003).…”
Section: Oxidative Stress Cholesterol and ω3 Fatty Acids In The Patmentioning
confidence: 99%